Accounting for the Concreteness and Neighborhood Effects in a High Frequency Word List for Poor Readers - Amanda Swee-Ching Tan; Farhan Ali (MDPI AG, 2023)
Some poor readers show little or no progress in literacy interventions as their susceptibility to the concreteness and neighborhood effect is not accounted for during intervention. This study aims to develop a resource for poor readers by revising the Dolch list to account for the concreteness and neighborhood (orthographic, phonological and semantic) effect. Psycholinguistic techniques were employed to recategorize 220 Dolch list words according to concreteness via function and content word categories, and include the associated orthographic, phonological and semantic neighbors of each word into a new High Frequency List with Neighbors (HFLN). One-way analysis of variance (ANOVA), Bonferroni post hoc test and Levene's test of variance homogeneity were carried out as measures of statistical significance and variability. The HFLN contains a total of 220 words with 1057 neighbors across five function and content word categories. Both measures of statistical significance and variability show that grade categories in the Dolch list contain greater mean concreteness values with overlapping similarities and higher variability. Conversely, the HFLN effectively delineates concreteness value clusters between categories with lower variability. The HFLN aids in targeted intervention of poor readers by presenting the available orthographic, phonological and semantic neighbors according to the descending order of concreteness.